Post genocide Rwanda: implications for cross-cultural police training - Willoughby-Mellors, Debra Lynn (2002)
Within a period of three months in 1994, up to one million people were killed as a result of war and genocide in Rwanda. Large numbers were physically and psychologically afflicted for life through maiming, rape and other trauma; over two million fled to neighbouring countries and half as many became internally displaced within Rwanda's borders. Post-genocide Rwanda is dramatically different from pre-genocide Rwanda; the genocide transformed the social, political and cultural landscape of Rwanda and undermined the trust that normally binds its people together. It was against this backdrop that I went to Rwanda in 1995 to engage in a process of action research with local stakeholders, in order to formulate, implement and evaluate a sustainable and effective police training programme. I was also able to reflect upon and research the issues of cultural transferability in a training context. This thesis therefore engages with both of those issues through a framework of the integrated theories of Weaver's `Colliding Icebergs' (1993) and Schein's Process Consultation (1987 and 1998). Weaver believes that entering another culture is similar to two colliding icebergs. The real clash occurs beneath the water where values and thought patterns conflict - the area that Schein describes as `Process' or, when deep-rooted and recurrent, `Structure', that is how things are done. The part of the iceberg that is above the surface would be described by Schein as the `Content' part of culture, that is what is done or the task that is to be achieved.